Extremely Low Birth Weight Infants - Nuntiyagul, Thunyagorn (Journal of Health Science of Thailand, 2018)
With advance technology on neonatal care and understanding of pathophysiology in preterm and low birth weight infants, the mortality rate of extremely low birth weight infants have declined. Even with collective efforts of obstetricians, pediatricians and nurses, and noble attitude towards the high risk infants, developing countries still do not fare well. Special care and attention are needed and dictate the need for capacity building for health manpower. This article covers clinical features and treatments of extremely low birth weight infants briefly as guideline of standard treatment and health care.